Peran Guru Pendidikan Agama Islam dalam Menanamkan Akidah Islamiyah pada Era Digitalisasi Siswa Kelas IX SMP Islam Ar-Riyadh Bontang Utara - Hashari, Yudi; Hamdani, Hamdani (NABAWI: Jurnal Penelitian Pendidikan Islam, 2025)
Aqidah is the foundation of faith for human life that believes in the existence of Allah, the subject of aqidah and akhlak functions to instill the aqidah of ahlussunnah wal jamaah which will later make students have a strong foundation of faith in facing the challenges of the times. The background of the research is about the role of aqidah in shaping the character of students who have noble morals. The purpose of this researcher is to find out how the role of Islamic religious education teachers is in instilling Islamic aqidah in the digitalization era and the role of Islamic religious education teachers in instilling Islamic aqidah in the digitalization era in class IX students of SMP Islam Ar-Riyadh Bontang Utara. This research method is qualitative with an observation, interview and documentation approach, then data analysis used data reduction, data presentation. The results of this study are that Aqidah Education should not be separated from the curriculum, especially in schools based on Islam because Aqidah Education not only strengthens the foundation of a person's faith but also functions as a tool in shaping the character of a student who is virtuous and noble. The conclusion of the results of this study shows that religious teachers play a very important role in maintaining the foundation of a student's faith and shaping the character of students in facing the changing times that can erode a person's faith.